Uji Psikometrik Instrumen Hots Untuk Siswa Kelas XI Pada Mata Pembelajaran Biologi - Nur Fitri Mitha Sayuti; Nurkhairo Hidayati (Jurnal Ilmu Pendidikan Biologi dan IPA, 2026)
This study aims to examine the psychometric quality of a Higher Order Thinking Skills (HOTS) instrument in Biology learning for eleventh-grade students, particularly on the topic of the human movement system. The research employed a quantitative approach using psychometric testing methods. The instrument consisted of 21 multiple-choice items developed based on the revised Bloom’s Taxonomy at cognitive levels C4 (analyzing), C5 (evaluating), and C6 (creating). The research participants were 40 eleventh-grade students of SMAN 1 Pekanbaru selected through simple random sampling. Data analysis included item validity testing, instrument reliability, difficulty index, and discrimination power. The results indicated that eight items were valid and suitable for use, several items required minor and major revisions, and three items were invalid and eliminated. The reliability coefficient obtained was 0.332, indicating low internal consistency; however, this result is still acceptable for a pilot test in an undergraduate research context. Overall, the HOTS instrument on the movement system topic requires further refinement to achieve better psychometric quality and to function effectively as an assessment tool for measuring students’ higher order thinking skills.